Why and when do some language-impaired children seem talkative? A study of initiation in conversations of children with semantic-pragmatic disorder - Bishop, Dorothy; Hartley, Joanne; Weir, Fiona (Journal of autism and developmental disorders, 1994)
Analysis of the conversations of 6 children (mean age 11 years) with semantic-pragmatic disorder found they were more likely to produce initiating utterances (rather than acknowledging or responding utterances) with both familiar and unfamiliar partners than other children of similar age or ability. Subjects did not produce more utterances or longer utterances than other children. (Author/DB)